Identificação, caracterização e avaliação da patogenicidade de diferentes isolados de fusarium spp. para o controle de thaumastocoris peregrinus (hemiptera: thaumastocoridae) - Velozo, Simone Graziele Moio [UNESP] (2015)
The bronze bug Thaumastocoris peregrinus Carpintero & Dellapé, 2006 (Hemiptera: Thaumastocoridae), invasive pest of Eucalyptus spp. (Myrtaceae) was reported in 2008 in Brazil. The symptoms caused by this pest are leaf silvering, leaf bronzing and defoliation in susceptible Eucalyptus species or clones. The main control strategies for T. peregrinus involve biological control with an egg parasitoid Cleruchoides noackae Lin & Huber, 2007 (Hymenoptera: Mymaridae), introduced from Australia and entomopathogenic fungi. These microorganisms show advantages such as via oral, traqueal or tegument infection, great genetic variability and remaining in the environment. The objective of this study were: identifying and characterizing entomopathogenic fungi collected from field epiziooties; running pathogenicity tests; molecular identification of fungi from sequencing of three regions in the genome (ITS-5.8S rDNA, β-Tubuline, α-elongase); cultural and morphological characterization of the isolates obtained; following up the colonization (externally) of fungi isolates when inoculated on the bronze bug with scanning and optical microscopy; verifying in vitro sensibility to fungicides normally used in eucalyptus plantations; analysing the phytopathogenicity of isolates to diferent plant species (tomato, sugarcane and Eucalyptus). The species obtained by molecular identification were: Fusarium proliferatum, F. tricinctum and F. equiseti. Pathogenicity test has proved that the isolates are letal to the bronze bug, being F. proliferatum (ISO-DPV-LCBPF004) e F. equiseti (ISO-DPV-LCBPF009) the most virulent ones and therefore selected for the other experiments. Fungicides Azoxystrobin + Cyproconazol (Priori Xtra®), Trifloxystrobin + Tebuconazole (Nativo®) and Pyraclostrobin (Comet®) were tested to verify sensibility. Isolates ISO-DPV-LCBPF004 e ISO-DPV-LCBPF009 of Fusarium spp. showed greater...